Economic and environmental appraisal of research and development project: new digestate treatment technology - Kubáňková, Marie; Hyršlová, Jaroslava; Ditl, Pavel (Melandrium, 2016)
Need to increase the intensity of agricultural production brings increased demand on policy makers´ decisions and agricultural practice. In this context in recent years has increased the importance of management tools and indicators for assessing and managing the farming activities. The subject of matter is the appraisal and management of not only the economic impacts, but also the environmental and social impacts. Input-output tables are used for various types of analysis. They were initially used for economical appraisal and later were extended to include more complex appraisal of the technology and working patterns and of new or substantially improved products. Within appraisal, the focus is not only on economic consequences but also on environmental and social aspects. The paper focuses on the economic and environmental appraisal of a particular outcome of a R&D project. With the growing number of biogas stations, there are in the literature increasingly emerging studies aimed to analyse the economic and environmental impacts of treatment of digestate, which is generated as a waste product of biogas production and is used in agriculture as fertilizer. The main aim of the paper is to present, using the balance models, economic and environmental appraisal of new digestate treatment technology.
Ekonomické a environmentální vyhodnocení výsledku projektu výzkumu a vývoje: Nová technologie úpravy digestátu
Keywords: research and development; environmental aspects; economic appraisal; digestate; výzkum a vývoj; environmentální aspekty; ekonomické hodnocení; digestát